Are Pre-Service Teachers Multicultural Thinkers as 21st Century Educators? - Kazu, Ibrahim Yasar; Yalcin, Cemre Kurtoglu (Fac Teacher Education, 2023)
Multicultural education is the harmonious coexistence of differences in terms of race, ethnicity, social class, religion, language, gender, and cultural characteristics in the educational setting. Multicultural education can be possible with teachers who are sensitive, aware of the existence of different cultures, respectful of differences and free from prejudices. This study aims to investigate the multicultural efficacy level of pre-service teachers. The data collection tool, 'The Multicultural Efficacy Scale' was applied to 588 pre-service teachers studying at the Faculty of Education at a public university in the 2021 - 2022 academic year. Three key aspects of their multicultural efficacy level were investigated: 'experience, attitude, and self-efficacy'. The overall multicultural efficacy level was found to be moderate. It was revealed that the pre -service teachers who live in metropolises, were included in pre-school education, have been abroad, and have a foreign friend have more multicultural experience. The study hopes to contribute to exhibiting the multicultural efficacy level of pre-service teachers. It has pedagogical implications for pre-service teachers in that they should be trained and given more knowledge about multicultural education so that they can meet the expectations of today's era.
Razmišljaju li budu?i u?itelji kao obrazovatelji 21. stolje?a multikulturno?
Keywords: attitude; experience; multicultural education; pre-service teachers; self-efficacy